Analysis of the Implementation of Regional Regulation No. 07 of 2017 concerning Street Children, Homeless and Beggars In Bengkulu City - Dimas Nugroho; Mulyadi Mulyadi; Budiman Sakti; Heru Purnawan (Journal of Social Science and Humanities, 2022)
The purpose of this research is to find out how the implementation of regional regulation (PERDA) no. 07 of 2017 about street children, homeless people and beggars in Bengkulu City. This study uses a qualitative descriptive method with data analysis techniques of observation, interviews and documentation. The informants in this study were the Bengkulu City Social Service, members of the Satpol, beggars, vagrants. Based on the results of the study, it can be concluded that communication has shown optimal results based on the fact that the research conducted has not been optimal in terms of transmission, clarity, and consistency when delivering information to policy implementers. Resources also show optimal results where aspects, information, authority are categorized as maximum, but for the aspect of facilities it is maximal because there are still many facilities needed or updated for parking attendants on duty and there are still frequent rejections from residents in terms of opening new parking lots and the staff aspect is still said not to be. optimal because there are still many illegal parking found. Disposition Showing the results that are less than optimal, it can be seen that the lack of facilities that support the implementation of the program. The bureaucratic structure is categorized as optimal based on research conducted with several informants saying that it is optimal in terms of work guidelines based on SOPs that are easily understood by policy implementers and carry out well.